Native American spiritualism : an exploration of indigenous beliefs and cultures - Arroyo, L. M. (Wellfleet Press, an imprint of The Quarto Group, 2023)
"The spiritual practices of Native Americans are as diverse and bountiful as the Nations themselves, renowned for their inextricable ties to nature and geographical location. Today, many Indigenous customs are still conflated and misunderstood, even throuogh their influence is seen and felt in every corner of the country."--